Comparison of two endogenous delivery agents in cancer therapy: Exosomes and ferritin. (August 2016) - Li, Le; Zhang, Lianbing; Knez, Mato
Graphical abstract: Abstract: Exosomes and ferritin: Two biomacromolecules from our human bodies both draw increasing interest for advanced drug delivery due to their endogenous origin and their morphology, the cage-like structures. They possess perfect naturally designed structures for loading and shielding of cargo. Their intrinsic biological functions enable a natural delivery of the load and specific targeting. More and more evidences point towards the evolution of a new era of drug delivery strategies with exosomes and ferritin, even for potential personalized therapy. This review focuses on the advantages as well as limits of exosomes and ferritin as endogenous carriers for cancer therapy. We compare their structure-specific cargo loading and their intrinsic cancer-related biological functions. Remaining challenges and promising perspectives for future development to use these two endogenous agents are discussed.